Biomarkers of inflammation and endothelial dysfunction in elderly patients with myocardial infarction, hypertension and frailty - N. M. Agarkov; O. I. Okhotnikov; A. V. Golikov; L. V. Kolpina; V. I. Kolomiets (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To analyze the level of biomarkers of inflammation and endothelial dysfunction in elderly patients with myocardial infarction (MI), hypertension (HTN) and frailty.Material and methods. Three following clinical groups were formed: patients aged 60-74 years with MI+ grade 1-2 HTN (n=80); patients aged 60-74 with MI+HTN+prefrailty (n=52); patients aged 60-74 years with MI+HTN+frailty (n=114). In patients of all groups 2-4 months after MI, the levels of high-sensitivity C-reactive protein (hsCRP), intercellular adhesion molecule 1 (ICAM-1), nitric oxide (NO) metabolites — nitrates and nitrites, endothelin-1, desquamated endotheliocytes, vascular endothelial growth factor (VEGF) were determined.Results. Patients with MI+HTN+frailty had a higher hsCRP — 6,4 mg/l compared with patients with MI+HTN+ prefrailty (4,2 mg/l; p<0,01) and patients with MI+HTN (3,2 mg/l; p<0,01). The level of ICAM-1 was 315,6, 242,7, and 213,5 ng/ml, respectively, in these groups (p<0,01). Patients with MI+HTN+prefrailty, MI+HTN+frailty and MI+HTN had following levels of nitrite (NO2-) and nitrate (NO3-) — 6,7, 5,4, and 7,2 pmol/l (p<0,01). A similar ratio is inherent in NO3-. On the contrary, the content of desquamated endotheliocytes and VEGF was significantly higher in patients with MI+HTN+frailty compared with patients with MI+HTN+ prefrailty (p<0,01). The level of endothelin-1 was also significantly higher in patients with MI+HTN+frailty compared with the MI+HTN+prefrailty group: 18,85 vs 13,41 fmol/l (p<0,05).Conclusion. The levels of inflammation and endothelial dysfunction in patients with MI+HTN are significantly higher than those in patients with MI+HTN+frailty compared with patients with MI+AH+prefrailty and MI+HTN, with the exception of nitric oxide metabolites.